COVID-19 Delta variation; more contagious or more pernicious? - Yazdanpanah, Fereshteh; Yazdanpanah, Shayan; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2022)
To the editor, Among the advancement of the COVID-19 pandemic, the pathogenic virus proceeds to change genomic epidemiology and steadily whole-genome sequencing evolution. One of the latest variations, SARS-CoV-2 delta, B.1.617.2 variant of concern (VOC) formerly, has become the most prevalent type of SARS-CoV-2 in many countries [1]. It identified following an upsurge in the western part of India since January 2021. More detailed analysis disclosed that the prevailing lineage in distribution is a novel identified lineage B.1.617 holding in common signature mutations D111D, G142D, L452R, E484Q, D614G, and P681R, in the spike protein, containing within the receptor-binding domain (RBD) [2, 3]. Following the initial high mortality rate of this variation in India as its hostess, as the growing number of fatal reports from several countries regarding its transfer to most parts of world in recent months, Delta variation was known as the deadliest COVID-19 [4, 5, 6]. According to official statistics, the mortality rate in individuals in areas where the Delta variant has become dominant is much higher than the same period and the epidemic with previous COVID-19 lineages. The enigma here is, does this mean more lethality of this variant?